Il regno del "prete Gianni" - D'Anna, Nuccio (Studi e materiali di storia delle religioni, 2008)
The text outlines the enigmatic figure of the "priest John" who has been the symbol of universal sovereignty all through the Middle Ages. There are also definite marks of the oriental origins from which such famous legend originates.